Digital Transformation, Student Satisfaction, Word of Mouth and Online Learning Intention in Vietnam - Dong Van Vu; Ghi Nha Tran; Cong Van Nguyen (Emerging Science Journal, 2022)
Objectives: To deal with the Covid-19 pandemic and its unpredictable variations, universities must develop many different response scenarios in which online teaching is considered a suitable, strategic, and long-term solution. Our study aims to investigate and determine the relationships between digital transformation, satisfaction, word-of-mouth communication, and students' intention to continue learning online in universities. Methods/Analysis: Our study uses Structural Equation Modeling (SEM) to measure the interaction with data processing tools such as partial least squares SEM (PLS-SEM), Cronbach's Alpha coefficient, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and PLS Bootstrapping with descriptive and inferential statistics. Findings: The results show a positive interaction between students, faculty, and schools with digital transformation; between digital transformation and student satisfaction and word of mouth communication; between satisfaction with an expression of mouth communication and the intention to continue learning online; and between oral communication and a student's intention to continue learning online. Novelty/Improvement: This is the first study to simultaneously identify, examine, and measure the impact of factors influencing digital transformation, student satisfaction, word-of-mouth communication, and the intention to continue online learning and their interrelationships.JEL Classification: A22, I20, I23 Doi: 10.28991/ESJ-2022-SIED-04 Full Text: PDF